Evolution of Reproductive Organs in Land Plants - Xin Wang (Frontiers Research Topics, 2018)
The great diversity of land plants (especially angiosperms) is mainly reflected in the diversity of various reproductive organs of plants. However, despite long time intensive investigations, there are still uncertainties and sometimes misunderstandings over the nature and evolution of reproductive organs in land plants. With the new advances made in various fields of botany (especially at molecular level), there is increasing light shed on some aspects of flowers (reproductive organs of angiosperms). In this ebook, we collect 15 papers reporting new understanding on plant reproductive organs. These works range from morphology and anatomy to molecular regulatory networks underlying traditional observations. We understand this single book cannot reach our goal, but we do hope that this book can contribute to or initiate some efforts leading to the final solution of some problems concerning the homology and evolution of reproductive organs in plants.